The influence of uncertainty and uncertainty tolerance on attitudes and self-efficacy about genomic tumor testing. Issue 7 (9th August 2021) - Anderson, Eric C.; Hinton, Alexandra; Lary, Christine W.; Strout, Tania; Antov, Andrey; Edelman, Emily; Helbig, Petra; Reed, Kate; Rueter, Jens; Han, Paul K.J.
ABSTRACT: Novel medical technologies, like large-panel genomic tumor testing (GTT), offer great promise but also substantial uncertainty regarding their clinical value and appropriate use. The goal of this study was to understand how clinicians' perceived uncertainty about GTT, and uncertainty tolerance (UT), a construct that describes trait-level differences in individuals' responses to uncertainty, influence attitudes and self-efficacy regarding GTT. Community-based oncologists participating in a study of large-panel GTT completed surveys assessing their perceptions of uncertainty about GTT, and their attitudes and self-efficacy regarding GTT. Multivariable regression analyses examined the relationship between oncologists' perceived uncertainty of GTT and their GTT-related attitudes and self-efficacy, and the potential moderating effect of individual differences in UT. Fifty-seven oncologists completed surveys. Greater perceived uncertainty about GTT was associated with more negative attitudes towards it. This association was moderated by UT, such that lower UT was associated with a stronger negative relationship between perceived uncertainty and attitudes. That is, oncologists who perceive GTT as uncertain, tended to have more negative attitudes, particularly if they were low in the trait of uncertainty tolerance. More research is warranted to understand how uncertainty and uncertainty tolerance influence clinicians' responses to GTT and other novel medical interventions.